Highway and rail transit tunnel maintenance and rehabilitation manual (Federal Highway Administration : Federal Transit Administration, 2004)
In March of 2001, the Federal Transit Administration (FTA) engaged Gannett Fleming, Inc., to develop the first ever Tunnel Management System to benefit both highway and rail transit tunnel owners throughout the United States and Puerto Rico. Specifically, these federal agencies, acting as ONE DOT, set a common goal to provide uniformity and consistency in assessing the physical condition of the various tunnel components. It is commonly understood that numerous tunnels in the United States are more than 50 years old and are beginning to show signs of considerable deterioration, especially due to water infiltration. In addition, it is desired that good maintenance and rehabilitation practices be presented that would aid tunnel owners in the repair of identified deficiencies. To accomplish these ONE DOT goals, Gannett Fleming, Inc., was tasked to produce an Inspection Manual, a Maintenance and Rehabilitation Manual, and a computerized database wherein all inventory, inspection, and repair data could be collected and stored for historical purposes. This manual is an update to the version issued in May, 2003. It provides specific information for the maintenance and rehabilitation of both highway and rail transit tunnels. Although several components are similar in both types of tunnels, a few elements are specific to either highway or rail transits tunnels, and are defined accordingly. The following paragraphs explain the specific subjects covered along with procedural recommendations that are contained in this manual.
Keywords: Tunnels -- Maintenance and repair.; Railroad tunnels -- Maintenance and repair.; Tunnels -- Inspection.; Railroad tunnels -- Inspection.; elektronické knihy; electronic books